PEMBINAAN KEPARIWISATAAN MELALUI PELATIHAN TEKNIK PRESENTASI KULINER LOKAL DI DESA WISATA MENGWI KECAMATAN MENGWI KABUPATEN BADUNG - Sutaguna, I.N.T.; Ariani, N.M.; Aryanti, N.N.S.; Putri, I.A.E.T. (Buletin Udayana Mengabdi, 2018)
Mengwi village has its special characteristic traditional foods ad beverages which can be developed as culinary tourism. Beside taste and the form of the foods , the cooking process from the ingredients until become the ready foods, and the presentation of the foods can be the interesting attraction to offer. Organizing the traditional food and beverages of Mengwi Village which is the part of the daily life in this village need to be measuring to be developed as the interaction tools and media among the local community and the tourist. The activities form such as; eating and enjoy the food together ( for lunch or dinner, etc ), organizing the restaurant, coffe shop, or cafe in the strategic location surround the village, cooking course for the women organization and the other programs. These programs of course need the education, training axercise and also the workshop how to make good presentation, improve the quality according to international standard, and also the sanitation and hygine. According to develop Mengwi Village become a Tourism Village as one of tourist object, the organizing traditional food and beverages business can be develop as the culinary tourism so that the local community can interacting directly with the tourist in Badung. The type of culinary which can be develop in Mengwi such as : Jukut Ares as a appetizer. Nasi Sela, Tipat Cantok, Betutu, Be Guling, Lawar Gedang, Jukut Urab as the main course. Tape Ketan and Jaje Uli, Jaje Dadar, Jaje Timus, Kolak Biu/Sela as the dessert. All of these culinary can be adapted to the international gastronomy from the form, purpose and essential so that can be presenting and offered to the tourist.